Dampak Hukum atas Kebijakan Kenaikan BBM pada PT Tameng Ditinjau dari Undang-Undang Nomor 20 Tahun 2008 tentang Usaha Mikro Kecil dan Menengah serta Dikali dari Teori Perlindungan Hukum - Hartono, Hartono; Heliany, Ina (Neolectura, 2025)
The fuel price increase in September 2022 had widespread impacts, including on Micro, Small, and Medium Enterprises (MSMEs), particularly those in the small-scale workshop services sector. MSMEs play a crucial role in the national economy, creating economic opportunities for low-income communities and reducing social inequality. This paper aims to analyze the impact of the fuel price increase on the revenue decline experienced by PT. Tameng, and link it to the regulatory framework under Law Number 20 of 2008 concerning MSMEs, as well as legal protection for small business owners. The methodology used is juridical-normative, analyzing written legal sources and relevant legislation.The findings show that the impact of the fuel price increase on PT. Tameng is significant, with a noticeable decline in revenue, directly reflecting the effects on small businesses. Article 7 of Law No. 20 of 2008 mandates the government to create a business climate conducive to the development of MSMEs. However, the fuel price hike policy has placed additional pressure on the small business sector, conflicting with the legal protection objectives. Therefore, a more sensitive evaluation of macroeconomic policies, considering the impact on vulnerable groups, is necessary.